Actual Aspects of Medical Application of Black Nut – Juglans Nigra L. (Review) - A. V. Korochinsky; Ja. V. Daironas; V. V. Vernikovsky; I. N. Zilfikarov; E. F. Stepanova; M. V. Chernikov (Разработка и регистрация лекарственных средств)
Introduction. Herbal drugs of black walnut (Juglans nigra L.) are not registered on the territory of the Russian Federation at the present time. However, the State Register of Medicinal Products includes an extract of unripe fruits of a related species walnut (Juglans regia L.) «Yuglanex» (made in Russia) and the complex herbal drug «Tonsilgon» (made in Germany). A number of biologically active food supplements from black walnut raw materials have been registered by Russian Federal Service for Surveillance on Consumer Rights Protection and Human Wellbeing. They are an additional source of phenolic compounds as tannins and flavonoids. The purpose of the article is to study and systematize up-to-date information on the chemical composition of the medicinal plant raw material of black walnut and the pharmacological properties of its main biologically active compounds.Text. All parts of the black walnut are used in the ethnomedicine of the indigenous population of North America according to indications similar to the walnut in Asia and the Manchurian nut in the Far East: snake bites, fever and disorders of the gastrointestinal tract.The chemical composition of the medicinal plant raw material of black walnut is dencently walnut by its qualitative composition. Fruits, bark and leaves of black walnut contain a rich polyphenol complex (naphthoquinones, in particular, juglon and its derivatives, tannins, flavonoids, phenolic acids), vitamins, essential oil, organic acids. However, the quantitative analysis revealed a higher content of biologically active substances in the raw black walnut, especially in relation to polyphenolic compounds.The scientific literature describes the results of experiments on animals, confirming antioxidant, antimicrobial, antifungal, antiviral, antiparasitic, hypoglycemic, antispasmodic, and anti-tumor effect on certain cell lines.Conclusion. As a result of studying the literature and systematizing the current information on the chemical composition of the medicinal plant raw material of the black nut and the pharmacological properties of its main biologically active compounds, it has been established that the main properties are related to the presence of the phenol complex. However, a deeper study of the chemical composition is required. Both the total extracts of the black walnut from plant raw materials and individual compounds show predominantly antimicrobial, antifungal, antioxidant, antiviral, hypotensive, immunomodulatory, antitumor and antispasmodic activities in preclinical trials.